SISTEM MONITORING PARAMETER BATERAI SEPEDA MOTOR LISTRIK BERBASIS IOT - Muhammad Tatag Titis Prabowo; Ery Muthoriq; Nanang Oktawidiandaru; Rifano Rifano (Pusat Penelitian dan pengabdian kepada Masyarakat (P3M) Politeknik Negeri Padang, 2026)
The rapid growth of electric vehicle adoption in Indonesia presents significant new challenges, particularly regarding the maintenance of energy storage systems, which remain the most critical components. Batteries in electric motorcycles are highly susceptible to premature degradation caused by unstable current and voltage parameters, as well as the high risk of uncontrolled temperature spikes that can trigger permanent damage or severe fire hazards. Consequently, intensive, continuous monitoring is an absolute necessity to ensure operational safety and reliability. This research focuses on developing a sophisticated prototype for a real-time electric motorcycle battery health monitoring system by integrating advanced Internet of Things (IoT) technology.The technical design of this device utilizes the high-performance ESP32 microcontroller as the primary processing unit, paired with a PZEM-017 sensor to monitor electrical variables and an RTD PT100 sensor with a MAX31865 module for precise temperature readings. All collected data is transmitted wirelessly to a dedicated cloud platform, allowing users to monitor battery status remotely via their smartphones. Furthermore, the system is equipped with an automated early warning feature via a Telegram bot, which instantly sends notifications when battery parameters fall outside safe limits, such as temperatures exceeding 35°C or voltage deviating from the optimal 42–57.6 V range.The methodology applied in this study is Research and Development (R&D) using the comprehensive ADDIE development framework. Based on a series of rigorous tests, the system demonstrated high levels of accuracy, with temperature reading success at 98.15% and voltage accuracy at 99.78%. Functional testing through the black-box method also proved that warning notifications were successfully delivered to the user's device with a perfect success rate. The implementation of this tool is expected to significantly assist users in performing preventive maintenance, thereby extending the battery's operational lifespan and overall energy